Keypoint lasting colorectal visit. A report on 819 consecutive outpatients - Zinicola, Roberto; Crafa, Pellegrino; Totaro, Anna Rita; Bonati, Elena; Del Rio, Paolo; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2024)
-